Longitudinal change in microRNA‐130a expression and its correlation with the risk of developing major adverse cardiovascular and cerebral events in patients undergoing continuous ambulatory peritoneal dialysis. Issue 12 (28th October 2021) - Wang, Hong; Xu, Jinglin; Wu, Xinhong; Zheng, Shouhao; Han, Yingmin; Ding, Guoming
Abstract: Background: MicroRNA‐130a (miR‐130a) regulates angio‐cellular dysregulation, atherosclerosis, and cardiocerebral injuries, serving as a biomarker for major adverse cardiovascular and cerebral events (MACCE) in several chronic diseases. However, its clinical application in patients with end‐stage renal disease (ESRD) undergoing continuous ambulatory peritoneal dialysis (CAPD), who are at a high risk of developing MACCE, has not been reported. Therefore, this study aimed to explore this aspect. Methods: miR‐130a expression in peripheral blood mononuclear cells obtained from 50 healthy controls (HCs) at recruitment and 257 ESRD patients undergoing CAPD at month (M)0, M12, M24, and M36 was determined by reverse transcription‐quantitative polymerase chain reaction. ESRD patients undergoing CAPD were followed up until MACCE occurred or M36. Then, MACCE were recorded, and MACCE‐free survival was calculated. Results: miR‐130a expression was significantly lower in ESRD patients undergoing CAPD than in HCs ( p  < 0.001). In addition, miR‐130a expression significantly decreased from M0 to M36 in ESRD patients undergoing CAPD ( p  < 0.001). Moreover, miR‐130a expression at M0, M12, and M24 was significantly lower in patients with MACCE than in those without MACCE (all p  < 0.05). Furthermore, high miR‐130a expression at M0, M12, and M36 was significantly correlated with prolonged MACCE‐free survival in ESRD patients undergoing CAPD (all p  < 0.05), and high miR‐130a expression at M0 was an independent factor for improved MACCE‐free survival ( p  = 0.015; hazard ratio (HR) (95% confidential interval): 0.456 (0.243–0.857)). Conclusion: miR‐130a expression decreases continuously with disease progression in patients with ESRD undergoing CAPD. Additionally, this expression is negatively correlated with MACCE risk in these patients. Abstract : miR‐130a decreases continuously with disease course in ESRD patients undergoing CAPD. Inspiringly, its expression negatively correlates with MACCE risk in these patients.